Monetary Policy Credibility and Exchange Rate Pass-Through in South Africa - Kabundi, Alain (IMF Working Papers; Working Paper, 2018)
This paper investigates the key factors that explain the documented decline in the exchange rate pass-through in South Africa over the past two decades, which coincides with the adoption of the inflation-targeting regime. The paper conjectures, in line with the literature, that this outcome is largely due to improved monetary policy credibility. To do this, it first documents the factors that explain monetary policy credibility. Using the standard deviation of individual inflation forecasts as a measure of monetary policy credibility, its shows that the latter is negatively affected by the level of inflation itself, monetary policy uncertainty, and a measure of the unobserved stochastic volatility of inflation. The second phase proceeds by analyzing the determinants of the pass-through using the monetary policy credibility index derived from the first phase. The paper confirms the remarkable achievement that, despite the many shocks that the economy has witnessed, the declining pass-through is indeed explained by the improving monetary policy credibility.